1999
DOI: 10.1002/(sici)1521-3935(19990401)200:4<719::aid-macp719>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of core coverage in core-shell particles by solid-state1H NMR spin-diffusion experiments

Abstract: SUMMARY:The shell material core coverages of two-phase core-shell particles are determined quantitatively by NMR spin-diffusion experiments. A simple relation is derived between the specific surface (ratio of core surface and core volume) and the core coverage of acrylic core-shell particles in the solid state. Through calibration with a reference sample of known core coverage, the core coverage of the other samples can then be evaluated. The values of core coverages determined by spin-diffusion become more ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…We decided to limit the number of cycles to six to avoid the loss of signal due to the existence of imperfect 90 8 pulses. [20] As we can see in Figure 4b, indeed the values of the g curve are superior to 1 and show a maximum for a radius of the particle around 28 nm. The two edges of the curve tend to reach a value of 1 as we move the selection towards the mobile core (small radius) or to the rigid shell (big radius).…”
Section: Characterisation Of the Interphasementioning
confidence: 52%
See 3 more Smart Citations
“…We decided to limit the number of cycles to six to avoid the loss of signal due to the existence of imperfect 90 8 pulses. [20] As we can see in Figure 4b, indeed the values of the g curve are superior to 1 and show a maximum for a radius of the particle around 28 nm. The two edges of the curve tend to reach a value of 1 as we move the selection towards the mobile core (small radius) or to the rigid shell (big radius).…”
Section: Characterisation Of the Interphasementioning
confidence: 52%
“…Used to compare the different samples, e9 represents a normalised interphase thickness as percentage of the outer radius of the particle. A10 40 14 13 10 -B20 45 17 17 18 13 C20 45 19 16 --D20 45 16 12 --E30 39 16 15 13 shell of one particle may then be in contact with the core of another [20] contributing to the increase in its apparent core-coverage factor f app measured by NMR. Table 4 shows the specific surface and the apparent core-coverage factor measured at 353 K for the 5 samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14,15,26] Our results are in line with other recent examples from the literature where it has been found that the NMR methods somewhat underestimate domain sizes. [7,[35][36][37] It is not clear at present what mechanisms may be responsible for the discrepancies, but it cannot be excluded that the microphase separation leads to increased dynamics at the interface that interfere with the spin diffusion processes. [32,33] Conclusion Solid-state NMR techniques were used to study microphase separated PI-b-PMMA diblock copolymers.…”
Section: Determination Of the Domain Sizes With Spin Diffusion Measurmentioning
confidence: 99%